The research and realization of vehicle license plate character segmentation and recognition technology - Jian-Xia Wang; Wan-Zhen Zhou; Jing-Fu Xue; Xin-Xin Liu (2010 International Conference on Wavelet Analysis and Pattern Recognition, 2010)
On the basis of the vehicle license plate location, an image grey vertical projection segmentation approach based on the distribution character segmentation is proposed in this paper. A two-stage approach consisting of coarse and accurate segmentation is adopted. It can increase the accuracy of the segmentation and has good segmentation speed. And in recognition process, character features are extracted from character segmentation results, in order to identify character exactly, an improved template matching method is used to character recognition. Experimental results show that character segmentation method is efficient and quick and recognition algorithm is applicable.